Application of pregelatinized suweg (Amorphopallus campanulatus BI) flour with moringa (Moringa oleifera) powder in noodles - Ekawati, I Gusti Ayu; Ina, Putu Timur; Pertiwi, I Desak Putu Kartika (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 3 No 1 (2016), 2016)
Raw materials in the noodle processing vary widely, addition is made from flour, noodle can also be processed from tubers such as suweg. This study aims to apply the use of pregelatinized suweg flour with Moringa powder in the processing of noodles. Pregelatinized suweg flour is used as a substitution wheat flour by 50%. In addition to using pregelatinized suweg flour, Moringa leaf powder is applied as an additive to improve the nutritional value and appeal of a wet noodle. This study uses a randomized complete design with ratio pregelatinized suweg flour and moringa powder is 50: 0; 45: 5; 40:10; 35:15; 30:20. The parameters observed nutrient content and sensory properties of a noodle. Noodles with a ratio between pregelatinized suweg flour and Moringa powder 40: 10 have the best characteristics. The nutritional value of noodle is water content of 38.72%, ash content of 0.87%, 3.86% protein content, fat content 16.17% , and carbohydrate content 40.39%, and the color sensory criteria (rather like), aroma (rather like), texture (normal), taste (normal), and overall acceptance (normal).
Keywords: : Pregelatinized suweg flour; moringa powder; wet noodles